Causal Factors Influencing the Purchase Intention of Cosmetics on the TikTok Shop Application of Consumers in Bangkok and Metropolitan Areas - Salee, Atittaya; Lexcharoen, Somchai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This research aims to 1) develop and validate the consistency of a causal relationship model with empirical data, and 2) investigate the causal factors influencing the purchase intention of cosmetics on the TikTok Shop application among consumers in the Bangkok Metropolitan Region. This quantitative study collected data via online questionnaires from a convenience sample of 430 consumers who had previously purchased products on the platform. The data were analyzed using descriptive statistics, Confirmatory Factor Analysis, and Structural Equation Modeling. The results revealed that the developed model fitted well with the empirical data. Awareness had the most significant direct effect on purchase intention ( = 0.424), followed by Engagement ( = 0.326), and Social Media Marketing ( = 0.262), respectively. Based on these findings, it is recommended that entrepreneurs focus on creating short-form video content featuring actual product demonstrations and user-generated reviews, alongside leveraging live streaming features. These actionable strategies will effectively stimulate consumer awareness and engagement, ultimately leading to higher purchase intention.